A Polyaniline-Coated Integrated Microfiber Resonator for UV Detection - Lim, K.S.; Chiam, Y.S.; Phang, S.W.; Chong, W.Y.; Pua, C.H.; Zulkifli, Ahmad Zarif; Ganesan, I.; Harun, Sulaiman Wadi; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2013)
We present a UV detector based on an integrated microfiber resonator. In fabrication, a thin layer of polyaniline (PAni) is deposited on a ~1-mm-diameter microfiber ring resonator-the sensing region of the detector. Red shift is observed in the output spectrum when PAni is irradiated with a UV light with a peak wavelength at 365 nm. This phenomenon can be due to the high absorbance in the UV region and photothermal effect of PAni. The wavelength shift is linearly proportional to the UV light intensity and the measured sensitivity is 6.61 nm/(W·cm-2).